New acid/base salts as co‐catalysts for the organocatalyzed ring opening polymerization of lactide. Issue 5 (17th December 2014) - Miao, Yong; Stanley, Nicholas; Favrelle, Audrey; Bousquet, Till; Bria, Marc; Mortreux, André; Zinck, Philippe
ABSTRACT (R)‐(+)‐binaphathyl‐diyl hydrogen phosphate (BNPH)/ diazabicyclo[5.4.0]undec‐7‐ene (DBU) and (1R)‐(−)−10‐camphorsulfonic acid (CSA)/4‐dimethylaminopyridine (DMAP) acid–base salts were synthesized and assessed for the ring‐opening polymerization of rac‐lactide. They were found to be inactive toward the polymerization in the presence of a protic initiator. When used in combination with a base such as DBU or DMAP and a protic initiator, these acid/base conjugates led to well‐controlled polymerization in mild conditions (DM < 1.1 in all cases). With DBU, the presence of the salt was found to lead to narrower molecular weight distributions than those obtained using the base alone, and to prevent undesirable transesterification reactions occurring at the end of the reaction. An increase in activity was observed using the salts in combination with DMAP as compared with DMAP alone, together with an improvement of the control over the molecular weight. The results were discussed on the basis of 1H nuclear magnetic resonance analyzes including acid/base equilibria involving the use of two different bases. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2015, 53, 659–664